Chemical composition and sensory properties of Caulerpa racemosa seaweed yellow noodle - Ahmad, Aziani; Zainol, Zamzila; Abdul Haiyee, Zaibunnisa; Mohd Nor, Norakma; Nazihah Mohamad Nizam, Nazatul; ., . (International Journal of Engineering and Technology, 2026)
Chemical composition and sensory properties of the dried Caulerpa racemosa collected from Port Dickson were determined. Addition of Caulerpa racemosa as an ingredient will enhance the nutritional composition of yellow noodle. In this study, the wheat flour that was used for the preparation of the noodles was partially substituted with the 20 g, 40 g and 60 g dried Caulerpa racemosa powder. The addition of Caulerpa racemosa powder in noodle increase the lipid and ash contents significantly (p
Keywords: Caulerpa Racemosa; Seaweed; Yellow Noodles; Proximate Analysis; Sensory.